Home Birth in the Era of COVID-19: Counseling and Preparation for Pregnant Persons Living with HIV - Premkumar, Ashish; Cassimatis, Irina; Berhie, Saba H.; Jao, Jennifer; Cohn, Susan E.; Sutton, Sarah H.; Condron, Brianne; Levesque, Jordan; Garcia, Patricia M.; Miller, Emily S.; Yee, Lynn M. (American Journal of Perinatology, 2020)
With the coronavirus disease 2019 (COVID-19) pandemic in the United States, a majority of states have instituted “shelter-in-place” policies effectively quarantining individuals—including pregnant persons—in their homes. Given the concern for COVID-19 acquisition in health care settings, pregnant persons with high-risk pregnancies—such as persons living with HIV (PLHIV)—are increasingly investigating the option of a home birth. Although we strongly recommend hospital birth for PLHIV, we discuss our experience and recommendations for counseling and preparation of pregnant PLHIV who may be considering home birth or at risk for unintentional home birth due to the pandemic. We also discuss issues associated with implementing a risk mitigation strategy involving high-risk births occurring at home during a pandemic.Key Points
Keywords: out-of-hospital birth; HIV; perinatal transmission; COVID-19